Aminoazobenzene and diaminoazobenzene functionalized graphene oxides as novel class of corrosion inhibitors for mild steel: Experimental and DFT studies - Gupta R.K.; Malviya M.; Verma C.; Quraishi M.A. (My University, 2025)
In the present work aminoazobenzene (AAB) and diaminobenzene (DAB) functionalized graphene oxide composites have been synthesized and characterized by their FT-IR, XRD, TEM, Raman and XPS spectra. The inhibition effect of these two functionalized graphene oxides was evaluated on mild steel corrosion in 1 M hydrochloric acid solution using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization methods. Electrochemical results showed that both the composites act as efficient corrosion inhibitors and their inhibition efficiencies increase with concentration. Aminoazobenzene functionalized graphene oxide (AAB-GO) and diaminobenzene functionalized graphene oxide (DAB-GO) exhibited maximum inhibition efficiencies of 94.65% and 92.04%, respectively at concentration as low as 25 mgL−1. Electrochemical impedance spectroscopy (EIS) study suggests that both investigated inhibitors inhibit mild steel corrosion by adsorbing on the metallic surface. Potentiodynamic polarization study suggests that studied composites act as mixed type inhibitors and predominantly behave as cathodic inhibitors. Scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), and energy dispersive X-ray spectroscopy (EDX) techniques were used for surface characterization. EDX analysis further confirmed the adsorption of inhibitors onto the metallic surface. The several DFT based indices such as EHOMO, ELUMO, energy band gap (ΔE; ELUMO–EHOMO), global hardness (η), softness (σ) and fraction of the electron transfer (ΔN) show that AAB-GO is a better inhibitor than DAB-GO. © 2017 Elsevier B.V.